Intersection Principles Between Islamic And International Humanitarian Law - Rufaida, Himmah A'la (Istinbath : Jurnal Hukum, 2019)
Abstract The universal nature as inherent in Islamic Law and International Humanitarian Law makes these two laws often compared. The comparison in terms of the principles between the two legal instruments is very interesting considering they both originate from two poles of thought which are always competing and without being insulated by space. There is no law that is permanent and final, that is what happened to those two legal methods. Law develops according to the era without reducing values. Islamic values were born much earlier than International Humanitarian Law. The basic principles of Islamic Law concerning the relationship of humanity in society between nations and nations during wars have become a strong foundation for international humanitarian law norms. For example, such as legal principles that contain the principles of equality, freedom, peace, humanity and so on